Enhancing Public Understanding of Riverbank Management and Regulations for Flood Control in Tabelo River - Mas Agastya, Dewandha; Setiawan, Ery; Yasa, I Wayan; Syntia Dewi, Evrianti (Pascasarjana Universitas Mataram, 2025)
Flood disasters in Kuta Village, Central Lombok Regency, are caused by high rainfall intensity, sedimentation, land-use changes, and low public awareness of river conservation. This study evaluates flood mitigation strategies for the Tabelo River through structural and non-structural approach. Hydrological analysis indicates that the river’s cross section is inadequate to handle flood discharge, leading to frequent overflows. Structural measures include sediment dredging to a depth of 1,45 m and constructing 4 m high embankments. Hydraulic modeling using HEC-RAS support these interventions to reduce flooding. Non-structural measures involve community outreach on riverbank regulations based on Ministerial Regulations No. 28 of 2015. This initiative aims to increase public awareness, prevent illegal riverbank constructions, and promote sustainable river management. The enforcement of riverbank regulations is expected to reduce flood risks, improve water quality, and minimize erosion and sedimentation. Additionally, educational posters have been developed to reinforce awareness of flood control and river construction. Integrating structural and non-structural strategies is crucial to mitigating floods and fostering environmental responsibility in Kuta Village.